United Republic of Tanzania : Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Requests for Waiver of Performance Criterion and Modification of Performance Criteria-Staff Report; Press Release; and Statement by the Executive Director for the United Republic of Tanzania. (IMF Staff Country Reports; Country Report ;, 2005)
This paper evaluates Tanzania's Third Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Requests for Waiver of Performance Criterion and Modification of Performance Criteria. Program objectives for the remainder of 2004/05 are fully achievable, but modest risks remain, particularly the vulnerability of the economy to unpredictable rainfall and pressures for more direct intervention by the government to address poverty alleviation. Tanzania's fiscal strategy remains focused on enhancing domestic resource mobilization and the quality of spending to support its poverty reduction goals.